The Devil's advocate : - Morley Iain
In the spring of 1979, fifteen-year-old Dana Scully is the new girl at school in Craiger, Maryland. But worse than that, her dreams--some of which, in the past, came true--have become more vivid and disturbing, and are haunted by a shadowy figure which could be an angel--or the devil. When a classmate who recently died in a car accident appears in Dana's dreams, she begins to investigate, uncovering more suspicious deaths. With the evidence mounting, she must face the dangerous knowledge that evil is real.